Auditing : assurance and risk - Knechel, W. Robert. (South-Western College, 2001)
An introduction to auditing and assurance. The role of auditing and assurance in a market economy. An overview of financial statement audits. Client acceptance and initial engagement planning. Understanding the client's business. Process analysis and risk assessment. Evaluating internal process controls. Business measurement and analytical evidence...